Value positions and relationships in the Swedish digital government - Leif Sundberg (Administrative Sciences, 2019)
Governments across the world spend vast resources on implementing digital technology. Electronic, or digital, government is the use and study of Internet-based information and communication technology in the public sector. A point of departure in this study is that investments in technology are not value-free; they require allocation of limited resources and trade-offs between values. The purpose of this paper was to investigate how values are prioritized in the Swedish digital government. This research was conducted by using quantitative data from a survey administered to Swedish municipalities and national agencies. In addition, qualitative data from a database was used to exemplify value operationalization. The research utilized a theoretical framework based on four value positions: professionalism, efficiency, service, and engagement. The findings reveal that service and quality, and productivity and legality have a high priority, while engagement values are less prioritized. Differences based on organization type and size are also discussed. Moreover, the study suggests that professionalism and efficiency are distinct value positions, while service and engagement are closely related through citizen centricity. The qualitative material suggests that citizen centricity can manifest itself as a form of service logic, but also in the form of educational digital inclusion activities for vulnerable groups. The paper concludes by suggesting that future research should further refine the concept of citizen centricity in relation to digital government values, since its current meaning is ambiguous.
Keywords: 350; digitalization; e-Government; public values